Enhanced properties for visible-light-driven photocatalysis of Ag nanoparticle modified Bi2MoO6 nanoplates - Anukorn Phuruangrat (2018)
© 2015 Elsevier Ltd. All rights reserved. The visible light driven Bi2MoO6 photocatalyst doped with different contents of Ag nanoparticles was successfully synthesized by a combination of hydrothermal and sonochemical methods. The as-synthesized samples were characterized by X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), scanning and transmission electron microscopy (SEM and TEM) and UV-visible spectroscopy to investigate crystalline structure, morphology, composition and photocatalytic properties. XRD patterns and TEM images of the samples revealed pure phase orthorhombic Bi2MoO6 nanoplates without any detection of Ag dopant due to its low concentration and very tiny particle size. TEM images showed that Ag nanoparticles with the size of 10-15 nm were dispersed randomly on the surface of Bi2MoO6. The XPS analysis of Ag/Bi2MoO6 nanocomposites revealed the presence of additional metallic Ag. Photocatalytic activities of the Ag/Bi2MoO6 nanocomposites were evaluated by determining the degradation of rhodamine B (RhB) under visible light radiation. In this research, the 10 wt% Ag/Bi2MoO6 nanocomposites showed the best photocatalytic activity. The results suggest that the dispersion of Ag nanoparticles on the surface of Bi2MoO6 significantly enhances its photocatalytic activity.